2021
DOI: 10.3390/biomedicines9010064
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy and Insulin Resistance of Epicardial Adipose Tissue Adipocytes: Association with the Coronary Artery Disease Severity

Abstract: Changes in the structural and functional characteristics of the epicardial adipose tissue (EAT) are recognized as one of the factors in the development of cardiometabolic diseases. However, the generally accepted quantitative assessment of the accumulation of EAT does not reflect the size of adipocyte and presence of adipocyte hypertrophy in this fat depot. Overall contribution of adipocyte hypertrophy to the development and progression of coronary atherosclerosis remains unexplored. Objective: To compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
(29 reference statements)
0
8
0
5
Order By: Relevance
“…Meanwhile, impaired kidney function may facilitate the accumulation of epicardial adipose tissue (EAT) ( 25 , 26 ). Although EAT is a source of adiponectin ( 27 ), it also secrets detrimental adipokines, such as leptin, to promote inflammation in adjacent coronary vascular beds, the accumulation of EAT has been associated with CAD severities ( 6 , 27 ). Therefore, based on the current understanding of adiponectin biology, it seems likely that the association of high serum adiponectin level with adverse CV outcomes indicates deteriorating kidney function in the natural course of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, impaired kidney function may facilitate the accumulation of epicardial adipose tissue (EAT) ( 25 , 26 ). Although EAT is a source of adiponectin ( 27 ), it also secrets detrimental adipokines, such as leptin, to promote inflammation in adjacent coronary vascular beds, the accumulation of EAT has been associated with CAD severities ( 6 , 27 ). Therefore, based on the current understanding of adiponectin biology, it seems likely that the association of high serum adiponectin level with adverse CV outcomes indicates deteriorating kidney function in the natural course of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, attention should be paid to the current tendency to study the relationship of CAD not only with the thickness and volume of EAT, but also with its structure and size of adipocytes [50,51]. One study has found that the size and degree of hypertrophy of the epicardial adipocytes are related to CAD severity [51].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Enlarged adipocytes have been shown to be the main cause of insulin resistance [ 54 , 55 ]. Small adipocytes counteract the metabolic disorders associated with obesity [ 56 , 57 , 58 ]. Expansion in size exposes adipocytes to mechanical stress due to increased contact with neighboring fat cells thus leading to hypoxia, while their further expansion makes them exceed the limits of oxygen diffusion.…”
Section: Adipogenesis and Pparγ Activitymentioning
confidence: 99%